2015
DOI: 10.1161/atvbaha.115.306245
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Cynomolgus Vascular Surrogate System for Preclinical Drug Assessment and Human Translation

Abstract: Cynomolgus macaques are highly responsive to atherogenic diets, and the atherogenic response is influenced by lipoprotein diet composition. Atherogenic diet-fed cynomolgus macaques develop coronary artery lesions, raised plasma cholesterol levels, and lesions of similar composition to humans. Atherosclerosis development in cynomolgus macaques is highly influenced by genetic predisposition, confounding diseases (such as diabetes mellitus), exercise, sex (increased susceptibility in men), and behavioral and psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 47 publications
(44 reference statements)
0
10
0
Order By: Relevance
“…The distribution and spread of data points reflects a greater number of genes that were differentially expressed at the supratherapeutic concentration (Total: 4954, Up-regulated: 2539, Down-regulated: 2415; p<0.01, FDR<10%) than the therapeutic concentration (Total: 2373 Up-regulated: 1110, Down-regulated: 1263; p<0.01). Analysis of the transcriptomic responses at both doses using the relative similarity index (RSI) methods described previously (Cole et al 2015; Feaver etl. 2016), revealed that a majority of the differentially expressed genes (DEGs) were regulated in the same direction (2238 genes; RSI>0.74) and only a small number (3 genes; RSI<−0.74) were regulated in opposite directions (Supplementary Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The distribution and spread of data points reflects a greater number of genes that were differentially expressed at the supratherapeutic concentration (Total: 4954, Up-regulated: 2539, Down-regulated: 2415; p<0.01, FDR<10%) than the therapeutic concentration (Total: 2373 Up-regulated: 1110, Down-regulated: 1263; p<0.01). Analysis of the transcriptomic responses at both doses using the relative similarity index (RSI) methods described previously (Cole et al 2015; Feaver etl. 2016), revealed that a majority of the differentially expressed genes (DEGs) were regulated in the same direction (2238 genes; RSI>0.74) and only a small number (3 genes; RSI<−0.74) were regulated in opposite directions (Supplementary Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Our data analysis algorithms have been previously published (Cole et al 2015; Feaver et al 2016). Briefly, following RNA deep sequencing, the reads were aligned to a standard hg19 human transcriptome using Bowtie 0.12.9 (Langmead and Salzberg, 2012) and the final gene counts calculated using eXpress v1.5.1 (Roberts et al 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, we assessed human iECs and iSMCs cocultured under vascular region-specific blood flow hemodynamics to determine if they display similar transcriptomic and functional responses to cocultures of primary human endothelial (pEC) and smooth muscle (pSMC) cells exposed to the same hemodynamics. We have previously demonstrated that this human vascular surrogate system utilizing cocultures of pEC:pSMC exposed to relevant hemodynamics mimics the in vivo endothelial and smooth muscle architecture, biology and physiology of the blood vessel wall, and is highly responsive to changes in hemodynamics, inflammatory milieu, and drug treatments [4][5][6]. Our results indicate that iPSC-derived vascular cells exhibit an immature phenotype and that hemodynamic coculture of iEC:iSMC restores a high degree of similarity to that of pEC:pSMC.…”
Section: Introductionmentioning
confidence: 99%
“…Our rigorous data analysis algorithms have been previously published(37). Briefly, following RNA deep sequencing, the reads were aligned to a standard hg19 human transcriptome.…”
Section: Methodsmentioning
confidence: 99%